EXTH-62. STEM CELL DELIVERY OF ONCOLYTIC ADENOVIRUS DNX-2401 FOLLOWING SURGICAL RESECTION FOR THE TREATMENT OF GLIOBLASTOMA. (11th November 2019) - Gopakumar, Sricharan; Gumin, Joy; Daou, Marc; Ledbetter, Daniel; McDonald, Malcolm; Hossain, Anwar; Hingtgen, Shawn; Ewend, Matthew; Lang, Frederick
Abstract: BACKGROUND: The oncolytic virus DNX-2401 (Delta-24-RGD) is a novel treatment of GBM. While prior studies have examined intratumoral injection of DNX-2401 into recurrent GBM, the potential of delivering DNX-2401 into the surgical resection cavity using tumor-tropic human mesenchymal stem cells (MSCs) has not been evaluated. We hypothesize that exploiting a fibrin-based scaffold for transplanting MSCs loaded with DNX-2401 (MSCs-DNX-2401) into the resection cavity will improve viral delivery, decrease GBM recurrence, and extend overall survival. METHODS: MSCs-DNX-2401 were seeded in a fibrin matrix or suspended in PBS and placed in the upper wells of transwell plates with U87 cells placed below. After one week, U87 cells were counted to compare rates of cellular killing and confirm release of DNX-2401 from fibrin-seeded MSCs. U87 cells were transduced with mCherry-Luciferase and implanted into the brains of athymic mice (N=16). After fluorescence-guided surgical resection of glioma xenografts, MSCs (control) or MSCs-DNX-2401 were delivered in the resection cavity using a fibrin scaffold. Serial bioluminescence imaging (BLI) was used to monitor tumor recurrence. RESULTS: In transwell experiments, MSCs-DNX-2401 seeded in fibrin were as effective as MSCs-DNX-2401 without the scaffold, indicating that fibrin did not negatively impact cell viability or viral release. In in vivo studies mimicking residual tumor after surgical resection, treatment of the post-resection cavity with MSCs-DNX-2401 suspended in fibrin permitted retention of MSCs-DNX-2401 within the tumor bed. Kaplan-Meier survival analyses revealed statistically significant improved survival after treatment with MSC-DNX-2401 in fibrin compared to controls with 50% of animals demonstrating complete responses according to BLI (p < 0.05). CONCLUSION: Delivering DNX-2401 into the post-resection surgical cavity using MSCs seeded in fibrin is capable of eradicating residual GBM and prolonging overall survival. These studies support the clinical translation of this approach in newly diagnosed patients undergoing surgical resection of GBM.